Fluorescence imaging for Fe3+ in Arabidopsis by using simple naphthalene-based ligands. Issue 59 (3rd June 2016) - Mun, Gyuri; Jung, Sung Ho; Ahn, Ahreum; Lee, Shim Sung; Choi, Myong Yong; Kim, Dong Hyeon; Kim, Jae-Yean; Jung, Jong Hwa
Abstract : Naphthalene-based probes1 and1A were found to dramatically decrease fluorescence upon addition of Fe 3+, but not with other metal ions. Furthermore, 1 and1A displayed high fluorescence quenched-imaging for Fe 3+ in Arabidopsis as well as nanofibruous films. Abstract : A main source of Fe 3+ exposure for mammals is through plant consumption. Thus, sensitive and selective Fe 3+ detection in plant tissue is a significant and an urgent need. Although fluorescence probes have been reported for Fe 3+ in water, the detection of endogenous biological Fe 3+ in plant tissue remains to be refined due to the high background signal and the thickness of the plant tissue that can hamper the effective application of traditional one-photon excitation. To address these issues, we have synthesized naphthalene-based probes, 1 and1A . Upon an addition of Fe 3+ in water–methanol (1 : 1, v/v, pH 7), the fluorescence probes of1 and1A were found to dramatically decrease, but no other metal ions had this effect. More interestingly, 1A, which had no diethyl 2, 2′-(phenylazanediyl)diacetate moiety, also exhibited high selectivity for Fe 3+ . These results clearly indicate that the Fe 3+ was bound to the nitrogen and oxygen atoms located near the naphthalene moiety. Furthermore, chemical probes of1 and1A were embedded into nanofibrous membrane films NF-1 and NF-1A, respectively, prepared by the electrospinning method for use as a portable chemical probe. Fluorescence changes were examined by immersing the films into solutions of various metal ions. The strong fluorescence intensity of both NF-1 and NF-1A dramatically decreased in accordance with concentration of Fe 3+ onto the film, which was a "turn-off" system. In contrast, no significant changes of fluorescence intensity were observed compared that of other metal ions, such as Na +, K +, Zn 2+, Pb 2+, Mn 2+, Cu 2+, Co 2+, Ca 2+, Fe 2+, and Cd 2+ . The results indicate that both NF-1 and NF-1A could be used to selectively detect Fe 3+ . We also investigated the practicality of both1 and1A as imaging probes for Fe 3+ to operate within living systems like plants. Chemical probes of both1 and1A were tested for fluorescence imaging of Fe 3+ in Arabidopsis . As expected, the fluorescence probes displayed high fluorescence imaging for Fe 3+ in Arabidopsis .